Graphene-aluminum magnesium hydrotalcite composite doping modified high-performance polyvinyl chloride and preparation method thereof

By using graphene-aluminum-magnesium hydrotalc composite doping modification technology in polyvinyl chloride, the shortcomings of polyvinyl chloride in thermal stability, aging resistance and flame retardant properties are solved, and the comprehensive performance of the material is improved.

CN119391105APending Publication Date: 2025-02-07YANGZHOU POLYTECHNIC INST
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411588513.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The existing polyvinyl chloride materials have shortcomings in thermal stability, aging resistance and flame retardant properties, and the addition of antioxidants will affect their mechanical properties.

Method used

Using graphene-aluminum-magnesium hydrotalcite composite doping modification technology, the coated doping modified graphene-aluminum-aluminum-magnesium hydrotalcite composite is prepared and added to the polyvinyl chloride system to improve the comprehensive performance of the material. .

Benefits of technology

It significantly improves the anti-aging performance, thermal stability, flame retardant properties and mechanical properties of polyvinyl chloride, extends its service life and broadens its application scenarios.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119391105A_ABST
    Figure CN119391105A_ABST
Patent Text Reader

Abstract

The invention discloses graphene-aluminum magnesium hydrotalcite composite doping modified high-performance polyvinyl chloride and a preparation method thereof. The high-performance polyvinyl chloride comprises the following raw material components in parts by weight: 100 parts of PVC resin; 3-5 parts of a heat stabilizer; 1-2 parts of a coupling agent; 14 parts of a plasticizer; and 8-26 parts of a coating doped modified graphene-aluminum magnesium hydrotalcite compound. The high-performance polyvinyl chloride disclosed by the invention has excellent aging resistance, thermal stability, flame retardance and mechanical property, and the excellent comprehensive performance of the high-performance polyvinyl chloride can improve the use effect of the high-performance polyvinyl chloride and broaden the application scene of the high-performance polyvinyl chloride; in the coated doped modified graphene-aluminum magnesium hydrotalcite compound, a composite structure system is formed by multiple components, so that the anti-aging performance, the thermal stability, the flame retardant property, the mechanical property and the like of a polyvinyl chloride material can be improved, and the effect of mutual cooperation and synergistic enhancement can be achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of polyvinyl chloride materials, and in particular to high-performance polyvinyl chloride modified by composite doping of graphene-aluminum-magnesium hydrotalcite and a preparation method thereof. Background Art

[0002] Polyvinyl chloride (PVC) is a material with light weight, excellent mechanical properties, corrosion resistance, waterproof and moisture-proof properties, and good chemical stability. It is widely used in pipes, various hollow products, injection molded products and other material fields. However, PVC has relatively poor thermal stability and aging resistance. In addition, PVC is not a completely safe fireproof material. When PVC burns, it produces a large amount of black smoke and toxic gases such as hydrogen chloride.

[0003] Although the addition of antioxidants helps to improve the aging resistance of PVC, there are compatibility issues between antioxidants and PVC (e.g., antioxidants containing benzene rings will increase the molecular distance between PVC molecules and reduce the intermolecular forces), resulting in a decrease in its mechanical properties. Therefore, the amount of antioxidants should not be too much. Patent CN118599242A discloses a method for preparing an aging-resistant polyvinyl chloride composite material, and CN111518345B discloses an aging-resistant polyvinyl chloride composite material and its preparation method, which can improve the aging resistance of polyvinyl chloride, but the comprehensive improvement effect is limited, and its flame retardant properties are not effectively improved.

[0004] Therefore, it is necessary to improve the existing technology to provide a more reliable solution. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide a high-performance polyvinyl chloride modified by composite doping of graphene-aluminum-magnesium hydrotalcite and a preparation method thereof in view of the deficiencies in the above-mentioned prior art.

[0006] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows: In the first aspect of the present invention, a high-performance polyvinyl chloride modified by composite doping of graphene-aluminum-magnesium hydrotalcite is provided, comprising the following raw material components in parts by weight: 100 parts of PVC resin; 3-5 parts of heat stabilizer; 1-2 parts of coupling agent; 5-14 parts of plasticizer; 8-26 parts of the coated doped modified graphene-aluminum-magnesium hydrotalcite composite.

[0007] Preferably, the heat stabilizer is at least one of calcium stearate, barium stearate and zinc stearate; The coupling agent is at least one of silane coupling agent KH560 and silane coupling agent KH570.

[0008] Preferably, the plasticizer is at least one of di(2-ethylhexyl) phthalate and epoxy soybean oil.

[0009] Preferably, the coated doped modified graphene-aluminum-magnesium hydrotalcite composite is prepared by the following steps: 1) Preparation of mesoporous alumina loaded with carbon dots; 2) Preparation of graphene oxide GO; 3) Preparation of reduced graphene oxide r-GO; 4) Preparation of doped modified graphene-aluminum-magnesium hydrotalcite composites; 5) The doped modified graphene-aluminum magnesium hydrotalcite composite is coated with an organic polymer to prepare a coated doped modified graphene-aluminum magnesium hydrotalcite composite.

[0010] Preferably, step 1) is specifically: 1-1) 0.5-3 g of polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer is added to 25-100 mL of ethanol, and then 2-9 mL of 35 wt% nitric acid aqueous solution and 1.75-7 g of aluminum isopropoxide are added, and the mixture is stirred for reaction for 15-30 min, and then dried at 50-80° C. for 12-36 h. The obtained product is calcined at 400-500° C. in an air atmosphere for 3-10 h to obtain mesoporous aluminum oxide; 1-2) Take 0.5-2g of mesoporous alumina and add it to 50-200mL of deionized water, and disperse it by ultrasonic for 5-30min. Then, add 0.1-0.5g of zinc acetate and disperse it by ultrasonic for 15-60min to obtain a mixed dispersion; 1-3) adding 172-688 mg of citric acid, 142-370 mg of lutein, 50-206 mg of diethylenetriamine, and 45-180 mg of urea to the mixed dispersion, and performing ultrasonic dispersion for 5-30 min to obtain a carbon dot precursor solution; 1-4) The obtained carbon dot precursor solution is transferred to a polytetrafluoroethylene-lined reactor, and the reaction is carried out at 175-210° C. for 5-24 hours. After the reaction is completed, the reaction is cooled to room temperature, the product is centrifuged, and the obtained solid product is vacuum dried at 70-100° C. for 6-24 hours to obtain mesoporous alumina loaded with carbon dots.

[0011] Preferably, step 2) specifically includes: 5-20g of graphite and 2.5-10g of sodium nitrate are added to 100-500mL of 98wt% concentrated sulfuric acid, and the mixture is stirred for reaction under ice bath conditions for 5-30min. Then, 17-70g of KMnO4 is added, and the mixture is stirred for 20-60min at 10-20°C, and the mixture is heated to 30-35°C, and the mixture is stirred for reaction for 5-20h. 200-800mL of deionized water is added to the product, and the mixture is heated to 90-98°C and maintained for 10-40min. Then, 200-800mL of deionized water and 2-10mL of 25wt% H2O2 solution are added in sequence, and the mixture is allowed to stand for 30-120min. After the system is separated into layers, the supernatant is removed, and the obtained product is washed with deionized water until neutralized, and then dried at 60-80°C for 12-36h to obtain graphene oxide GO.

[0012] Preferably, step 3) specifically includes: Take 0.5-2g of graphene oxide and add it to 25-100mL DMF solution, ultrasonically disperse it for 15-60min, then add it to 5-30mL ethylenediamine, stir and reflux at 70-90°C for 12-48h, filter the product, wash it with DMF and ethanol in turn, vacuum dry it at 60-90°C for 6-24h, grind it to obtain reduced graphite oxide.

[0013] Preferably, step 4) is specifically: 4-1) Take 2.6-11g of Mg(NO3)2·6H2O, 3.5-15g of Al(NO3)2·9H2O, and 1.25-5g of sodium citrate and add them to 300-1200mL of deionized water, and ultrasonicate for 10-30min to obtain precursor solution 1; 4-2) 1.25-5g of carbon dot-loaded mesoporous alumina and 1.9-7.6g of r-GO were added into 250-1000mL of deionized water, and ultrasonically dispersed for 10-60min. Then, 0.35-1.5g of Ce(NO3)3 was added, and stirred at 500-2000rpm for 10-60min to obtain precursor solution 2; 4-3) Precursor solution 1 is added to precursor solution 2 under stirring, the pH value of the system is adjusted to 9.5-10.5 with an alkaline solution, ultrasonicated for 30-120 minutes, and the resulting mixture is transferred to a polytetrafluoroethylene-lined reactor, reacted at 130-150° C. for 6-24 hours, filtered after the reaction, and the solid product is washed with deionized water until neutral, vacuum dried at 60-90° C. for 6-24 hours, and ground to obtain a doped modified graphene-aluminum magnesium hydrotalcite composite; The alkaline solution is a mixture of NaOH and Na2CO3 in deionized water, wherein the concentration of NaOH is 0.5-2 mol / L and the concentration of Na2CO3 is 0.25-1 mol / L.

[0014] Preferably, step 5) specifically includes: 5-1) 2-8 g of acrylic acid, 1.7-7 g of methyl methacrylate, and 1.7-7 g of butyl acrylate were added to 40-160 mL of a mixed solution consisting of deionized water and ethanol in a volume ratio of 1:1, and stirred for 5-20 min to obtain a mixture 1; 5-2) 1-4 g of the doped modified graphene-aluminum magnesium hydrotalcite composite, 0.4-1.6 g of fatty alcohol polyoxyethylene ether ammonium sulfate, and 50-200 mL of ethanol were added into 75-300 mL of deionized water, and stirred at 400-1500 rpm for 30-90 min to obtain a mixture 2; 5-3) Add 1 / 3 of the mass of mixture 1 to the mixed solution 2 under stirring, continue stirring for 5-30 minutes, add 0.04-0.16g of potassium persulfate, and then heat to 65-72°C and react for 0.5-2h; add the remaining mixture 1 dropwise to the product of step 1 under stirring, and complete the addition within 1-3h, then add 0.05-0.2g of potassium persulfate, raise the temperature to 73-78°C, and react for 1.5-6h to obtain a coated doped modified graphene-aluminum magnesium hydrotalcite composite.

[0015] The second aspect of the present invention provides a method for preparing the high-performance polyvinyl chloride modified by the composite doping of graphene-aluminum-magnesium hydrotalcite as described above, comprising the following steps: The PVC resin, heat stabilizer, coupling agent, plasticizer and coated doped modified graphene-aluminum magnesium hydrotalcite composite are stirred at a rotation speed of 400-1200 rpm for 15-60 minutes, and the obtained mixture is kneaded at 150-170° C. for 5-30 minutes to obtain high-performance polyvinyl chloride doped and modified by graphene-aluminum magnesium binary hydrotalcite composite.

[0016] The beneficial effects of the present invention are: The present invention adds the coated doped modified graphene-aluminum-magnesium hydrotalcite composite as a multi-effect modified filler into the polyvinyl chloride system to prepare a high-performance polyvinyl chloride, which has excellent anti-aging performance, thermal stability, flame retardant performance and mechanical properties. Its excellent comprehensive performance can improve its use effect and broaden its application scenarios. In the coated doped modified graphene-aluminum-magnesium hydrotalcite composite of the present invention, a composite structural system is formed by multiple components, which can play a role of mutual cooperation and synergistic enhancement in improving the anti-aging performance, thermal stability, flame retardancy and mechanical properties of polyvinyl chloride materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1The free radical scavenging ability test results of the carbon dot-loaded mesoporous alumina (Al2O3@Zn-CDs) prepared in Example 1 and the carbon dot-loaded mesoporous alumina (Al2O3@CDs) prepared in Comparative Example 3; Figure 2 The tensile strength test results of the high performance polyvinyl chloride prepared in Examples 1-4 and Comparative Examples 1-4; Figure 3 The bending strength test results of the high performance polyvinyl chloride prepared in Examples 1-4 and Comparative Examples 1-4; Figure 4 The limiting oxygen index test results of the high performance polyvinyl chloride prepared in Examples 1-4 and Comparative Examples 1-4; Figure 5 The heat deformation temperature test results of high performance polyvinyl chloride prepared in Examples 1-4 and Comparative Examples 1-4; Figure 6 The test results of the tensile strength retention rate of the high-performance polyvinyl chloride prepared in Examples 1-4 and Comparative Examples 1-4 after thermal aging; Figure 7 These are the test results of the flexural strength retention rate of the high-performance polyvinyl chloride prepared in Examples 1-4 and Comparative Examples 1-4 after thermal aging. DETAILED DESCRIPTION

[0018] The present invention is further described in detail below in conjunction with embodiments so that those skilled in the art can implement the invention with reference to the description.

[0019] It should be understood that the terms such as “having”, “including” and “comprising” used herein do not exclude the existence or addition of one or more other elements or combinations thereof.

[0020] The test methods used in the following examples are conventional methods unless otherwise specified. The materials and reagents used in the following examples are all commercially available unless otherwise specified. In the following examples, if no specific conditions are specified, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used, if the manufacturer is not specified, are all conventional products that can be purchased commercially.

[0021] The present invention provides a high-performance polyvinyl chloride modified by composite doping of graphene-aluminum-magnesium hydrotalcite, comprising the following raw material components in parts by weight: 100 parts of PVC resin; 3-5 parts of heat stabilizer; 1-2 parts of coupling agent; 5-14 parts of plasticizer; 8-26 parts of the coated doped modified graphene-aluminum-magnesium hydrotalcite composite.

[0022] In a preferred embodiment, the heat stabilizer is at least one of calcium stearate, barium stearate and zinc stearate; in a more preferred embodiment, the heat stabilizer is a mixture of calcium stearate and barium stearate in a mass ratio of 1:1.

[0023] In a preferred embodiment, the coupling agent is at least one of silane coupling agent KH560 and silane coupling agent KH570.

[0024] In a preferred embodiment, the plasticizer is at least one of di(2-ethylhexyl) phthalate and epoxy soybean oil.

[0025] In a preferred embodiment, the coated doped modified graphene-aluminum-magnesium hydrotalcite composite is prepared by the following steps: 1) Preparation of mesoporous alumina loaded with carbon dots: 1-1) 0.5-3 g of polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer is added to 25-100 mL of ethanol, and then 2-9 mL of 35 wt% nitric acid aqueous solution and 1.75-7 g of aluminum isopropoxide are added, and the mixture is stirred for reaction for 15-30 min, and then dried at 50-80° C. for 12-36 h. The obtained product is calcined at 400-500° C. in an air atmosphere for 3-10 h to obtain mesoporous aluminum oxide; 1-2) Take 0.5-2g of mesoporous alumina and add it to 50-200mL of deionized water, and disperse it by ultrasonic for 5-30min. Then, add 0.1-0.5g of zinc acetate and disperse it by ultrasonic for 15-60min to obtain a mixed dispersion; 1-3) adding 172-688 mg of citric acid, 142-370 mg of lutein, 50-206 mg of diethylenetriamine, and 45-180 mg of urea to the mixed dispersion, and performing ultrasonic dispersion for 5-30 min to obtain a carbon dot precursor solution; 1-4) The obtained carbon dot precursor solution is transferred to a polytetrafluoroethylene-lined reactor, and the reaction is carried out at 175-210° C. for 5-24 hours. After the reaction is completed, the reaction is cooled to room temperature, the product is centrifuged, and the obtained solid product is vacuum dried at 70-100° C. for 6-24 hours to obtain mesoporous alumina loaded with carbon dots.

[0026] 2) Preparation of graphene oxide GO: 5-20g of graphite and 2.5-10g of sodium nitrate are added to 100-500mL of 98wt% concentrated sulfuric acid, and the mixture is stirred for reaction under ice bath conditions for 5-30min. Then, 17-70g of KMnO4 is added, and the mixture is stirred for 20-60min at 10-20°C, and the mixture is heated to 30-35°C, and the mixture is stirred for reaction for 5-20h. 200-800mL of deionized water is added to the product, and the mixture is heated to 90-98°C and maintained for 10-40min. Then, 200-800mL of deionized water and 2-10mL of 25wt% H2O2 solution are added in sequence, and the mixture is allowed to stand for 30-120min. After the system is separated into layers, the supernatant is removed, and the obtained product is washed with deionized water until neutralized, and then dried at 60-80°C for 12-36h to obtain graphene oxide GO.

[0027] 3) Preparation of reduced graphene oxide r-GO: Take 0.5-2g of graphene oxide and add it to 25-100mL DMF solution, ultrasonically disperse it for 15-60min, then add it to 5-30mL ethylenediamine, stir and reflux at 70-90°C for 12-48h, filter the product, wash it with DMF and ethanol in turn, vacuum dry it at 60-90°C for 6-24h, grind it to obtain reduced graphite oxide.

[0028] 4) Preparation of doped modified graphene-aluminum-magnesium hydrotalcite composites: 4-1) Take 2.6-11g of Mg(NO3)2·6H2O, 3.5-15g of Al(NO3)2·9H2O, and 1.25-5g of sodium citrate and add them to 300-1200mL of deionized water, and ultrasonicate for 10-30min to obtain precursor solution 1; 4-2) 1.25-5g of carbon dot-loaded mesoporous alumina and 1.9-7.6g of r-GO were added into 250-1000mL of deionized water, and ultrasonically dispersed for 10-60min. Then, 0.35-1.5g of Ce(NO3)3 was added, and stirred at 500-2000rpm for 10-60min to obtain precursor solution 2; 4-3) Precursor solution 1 is added to precursor solution 2 under stirring, the pH value of the system is adjusted to 9.5-10.5 with an alkaline solution, ultrasonicated for 30-120 minutes, and the resulting mixture is transferred to a polytetrafluoroethylene-lined reactor, reacted at 130-150° C. for 6-24 hours, filtered after the reaction, and the solid product is washed with deionized water until neutral, vacuum dried at 60-90° C. for 6-24 hours, and ground to obtain a doped modified graphene-aluminum magnesium hydrotalcite composite; The alkaline solution is a mixture of NaOH and Na2CO3 in deionized water, wherein the concentration of NaOH is 0.5-2 mol / L and the concentration of Na2CO3 is 0.25-1 mol / L.

[0029] 5) The doped modified graphene-aluminum magnesium hydrotalcite composite is coated with an organic polymer to obtain a coated doped modified graphene-aluminum magnesium hydrotalcite composite: 5-1) 2-8 g of acrylic acid, 1.7-7 g of methyl methacrylate, and 1.7-7 g of butyl acrylate were added to 40-160 mL of a mixed solution consisting of deionized water and ethanol in a volume ratio of 1:1, and stirred for 5-20 min to obtain a mixture 1; 5-2) 1-4 g of the doped modified graphene-aluminum magnesium hydrotalcite composite, 0.4-1.6 g of fatty alcohol polyoxyethylene ether ammonium sulfate, and 50-200 mL of ethanol were added into 75-300 mL of deionized water, and stirred at 400-1500 rpm for 30-90 min to obtain a mixture 2; 5-3) Add 1 / 3 of the mass of mixture 1 to the mixed solution 2 under stirring, continue stirring for 5-30 minutes, add 0.04-0.16g of potassium persulfate, and then heat to 65-72°C and react for 0.5-2h; add the remaining mixture 1 dropwise to the product of step 1 under stirring, and complete the addition within 1-3h, then add 0.05-0.2g of potassium persulfate, raise the temperature to 73-78°C, and react for 1.5-6h to obtain a coated doped modified graphene-aluminum magnesium hydrotalcite composite.

[0030] The present invention also provides a method for preparing the above graphene-aluminum-magnesium hydrotalcite composite doped and modified high-performance polyvinyl chloride, comprising the following steps: The PVC resin, heat stabilizer, coupling agent, plasticizer and coated doped modified graphene-aluminum magnesium hydrotalcite composite are stirred at a rotation speed of 400-1200 rpm for 15-60 minutes, and the obtained mixture is kneaded at 150-170° C. for 5-30 minutes to obtain high-performance polyvinyl chloride doped and modified by graphene-aluminum magnesium binary hydrotalcite composite.

[0031] The present invention adds the coated doped modified graphene-aluminum-magnesium hydrotalcite composite as a multi-effect modified filler into the polyvinyl chloride system, which can significantly improve the anti-aging performance, thermal stability, flame retardancy and mechanical properties of the polyvinyl chloride material, and can effectively improve the comprehensive performance of the polyvinyl chloride composite material. The main mechanism thereof is described below in combination with a specific preparation method to facilitate understanding of the present invention.

[0032] 1. In the present invention, mesoporous alumina with rich pore structure is first prepared, and then zinc-doped carbon dots are in situ loaded on the surface of the mesoporous alumina to obtain mesoporous alumina loaded with carbon dots: Al2O3@Zn-CDs; the carbon dots are synthesized by a one-pot hydrothermal method using citric acid, lutein, diethylenetriamine and urea as raw materials, and the surface of the carbon dots has rich functional groups such as amino, carboxyl, and hydroxyl, and it has well inherited the reducing properties of lutein and diethylenetriamine, can scavenge free radicals, and exhibits excellent antioxidant properties.

[0033] 2. Then, graphene oxide GO was synthesized by the improved Hummers method, and r-GO was prepared by reducing GO with ethylenediamine, which was conducive to the interlacing of polyvinyl chloride molecular chains between graphite sheets; 3. Then, a one-pot method was used to prepare the modified hydrotalcite filler coated with r-GO and loaded with carbon dots, mesoporous alumina and rare earth cerium composite doped: r-GO@-Ce-Al2O3@Zn-CDs-LDHs. In this process, Ce 3+ On the one hand, Ce is added into the magnesium-aluminum hydrotalcite system, and on the other hand, 3+ It can coordinate with the amino, carboxyl, hydroxyl and other functional groups on the surface of carbon dots and the hydroxyl and other functional groups on the surface of r-GO, thus playing the role of an intermediate bridge, so that the mesoporous aluminum oxide loaded with carbon dots is grafted to the surface of r-GO, thereby forming a composite structure system of r-GO coated LDHs, Ce doped in LDHs, and Al2O3@Zn-CDs grafted on r-GO, that is, a doped modified graphene-aluminum-magnesium hydrotalcite composite; 4. Finally, acrylic acid, methyl methacrylate and butyl acrylate are used as mixed monomers and potassium persulfate is used as an initiator to polymerize on the surface of the doped modified graphene-aluminum magnesium hydrotalcite composite to form a polyacrylate organic coating layer, thereby obtaining a coated doped modified graphene-aluminum magnesium hydrotalcite composite.

[0034] In the structural system of the coated doped modified graphene-aluminum-magnesium hydrotalcite composite, the main action mechanism of each component is as follows: The mechanism of PVC aging is mainly a free radical chain reaction caused by thermal degradation. According to this mechanism, the double bonds, branching points, residual initiator groups and oxygen-containing structures in PVC generate free radicals under the stimulation of heat or light. These free radicals trigger a chain reaction in PVC, leading to dehydrochlorination and degradation. The double bonds formed by dehydrochlorination are very active and will continue to generate conjugated double bonds, resulting in discoloration of PVC (Guo Yixuan, Li Dianqing, Tang Pinggui, et al. Research Progress on the Application of Hydrotalcite Thermal Stabilizers in Polyvinyl Chloride [J]. Plastic Additives, 2020(1):14.DOI:CNKI:SUN:SLZJ.0.2020-01-002.). The newly generated free radicals can further trigger the degradation of PVC and intensify the degradation reaction. Therefore, PVC degradation can be divided into two main stages: the first stage is a violent dehydrochlorination process, which generates free radicals at the same time; the second stage is the cracking of the polyolefin structure in the molecular chain. Removing free radicals and HCl generated in the PVC system is an effective means to improve the thermal stability of PVC and enhance its anti-aging performance. The present invention improves the anti-aging performance and thermal stability of PVC from these two aspects.

[0035] (1) Magnesium aluminum hydrotalcite LDHs have a special layered structure and chemical composition, which makes them a non-toxic, cheap and efficient PVC thermal stabilizer. The unique layered structure and porous structure of hydrotalcite can effectively absorb HCl produced by the thermal decomposition of PVC, thereby improving the thermal stability of PVC (Liu Zhaonian, Wang Zhen, Gu Zhaohui, et al. Progress in hydrotalcite and its application in polyvinyl chloride [J]. Plastics, 2021(005):050.). On the other hand, LDHs also have excellent flame retardant and smoke suppression properties. The flame retardant mechanism of LDHs can be attributed to the combination of the following three functions: heat absorption, gas dilution and carbonization (Qiao Peng. Preparation of rare earth hydrotalcite / graphene oxide hybrid materials and research on flame retardant TPU [D]. Qingdao University of Science and Technology, 2020.).

[0036] (2) The carbon dots in Al2O3@Zn-CDs have excellent reducing properties and can scavenge free radicals. When combined with LDHs, they can greatly reduce HCl and free radicals in the PVC system, thereby preventing further decomposition of PVC and improving its stability and anti-aging properties. Furthermore, the carbon dots are loaded in the pore structure of mesoporous alumina and finally coated with polyacrylate to form a good sustained-release system, which can provide long-lasting free radical capacity and prolong the duration of anti-aging effects. At the same time, when free radicals are generated in the system, the action of the free radicals will cause the polyacrylate coating layer to break, and adaptively accelerate the scavenging efficiency of the carbon dots on the mesoporous alumina. The doping of Zn in the carbon dots can enhance their ability to scavenge free radicals and also enhance the thermal stability of PVC.

[0037] On the one hand, mesoporous alumina provides loading and sustained-release functions. On the other hand, with its excellent heat resistance and mechanical strength, it can also improve the thermal stability and mechanical properties of PVC to a certain extent.

[0038] (3) Reduced graphene oxide (rGO) is a material that is obtained by reducing graphene oxide (GO) to graphene through a reduction reaction. GO is a graphene derivative with oxygen-containing functional groups and is chemically active. The rGO obtained after reduction has fewer oxidized functional groups, an increased degree of reduction, and is more chemically stable than GO. rGO has excellent mechanical strength, thermal conductivity, and thermal conductivity, which can improve the mechanical properties of PVC, and can play a role in carbonization and physical barrier in the system, thereby improving flame retardancy.

[0039] (4) Inorganic materials such as magnesium aluminum hydrotalcite, reduced graphene oxide and mesoporous aluminum oxide all have the defects of agglomeration and difficulty in uniformly dispersing in organic systems when used in PVC organic materials.

[0040] The present invention can well overcome the above-mentioned defects by constructing a special coated doped modified graphene-aluminum-magnesium hydrotalcite composite structure system: Firstly, a multi-component composite structure system was formed by coating LDHs with r-GO, doping Ce into LDHs, and grafting Al2O3@Zn-CDs onto r-GO: a doped and modified graphene-aluminum-magnesium hydrotalcite composite was obtained, and then polyacrylate was coated to obtain a coated, doped and modified graphene-aluminum-magnesium hydrotalcite composite; the coating effect of the polyacrylate organic film can greatly improve the compatibility with the PVC organic system and achieve uniform dispersion; at the same time, the polyacrylate itself can toughen PVC, improve processing performance and impact resistance, etc.

[0041] (5) The doping of rare earth Ce plays an intermediate bridging role in the preparation of doped modified graphene-aluminum magnesium hydrotalcite composites. On the other hand, Ce has many empty 4f and 5d orbitals, which can act as a central ion to form coordination bonds with unstable chlorine atoms on the PVC main chain, making the carbon-chlorine bond stable and not easy to break, slowing down the thermal degradation of PVC, thereby further improving the thermal stability of PVC.

[0042] Therefore, in the coated doped modified graphene-aluminum-magnesium hydrotalcite composite of the present invention, a composite structural system is formed by multiple components, which can play a role of mutual cooperation and synergistic enhancement in improving the anti-aging performance, thermal stability, flame retardancy and mechanical properties of polyvinyl chloride materials.

[0043] The above is the overall concept of the present invention, and detailed embodiments and comparative examples are provided below on the basis of the overall concept of the present invention to further illustrate the present invention.

[0044] The sources of some of the raw materials involved in the following examples and comparative examples are as follows: PVC resin, brand: German vinnolit, purchased from Shanghai Honglei Plastic Chemical Co., Ltd.; Epoxidized soybean oil (ESO), Jiangsu Yuntong New Material Technology Co., Ltd.; Silane coupling agent KH560, Nanjing Roen Silicon Materials Co., Ltd.; Calcium stearate, barium stearate, Nantong Runfeng Petrochemical Co., Ltd. Fatty alcohol polyoxyethylene ether ammonium sulfate, Jiangsu Runfeng Synthetic Technology Co., Ltd.; Polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer (P123), Beijing Beike New Materials Technology Co., Ltd.

[0045] Example 1 A high-performance polyvinyl chloride modified by composite doping of graphene-aluminum-magnesium hydrotalcite comprises the following raw material components in parts by weight: 100 parts of PVC resin; 4 parts of heat stabilizer; 2 parts of coupling agent; Plasticizer 7 parts; 21 parts of coated doped modified graphene-aluminum-magnesium hydrotalcite composite.

[0046] The heat stabilizer is a mixture of calcium stearate and barium stearate in a mass ratio of 1:1, the coupling agent is silane coupling agent KH560, and the plasticizer is epoxy soybean oil.

[0047] The preparation method of the graphene-aluminum-magnesium hydrotalcite composite doped and modified high-performance polyvinyl chloride is as follows: According to the above weight ratio, PVC resin, heat stabilizer, coupling agent, plasticizer and coated doped modified graphene-aluminum-magnesium hydrotalcite composite were added to a mixer and stirred at 800 rpm for 30 minutes. The resulting mixture was added to an open mill and mixed at 165° C. for 20 minutes to obtain high-performance polyvinyl chloride doped and modified by graphene-aluminum-magnesium binary hydrotalcite composite.

[0048] The coated doped modified graphene-aluminum magnesium hydrotalcite composite is prepared by the following steps: 1) Preparation of mesoporous alumina loaded with carbon dots: 1-1) 1.5 g of polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer was added to 50 mL of ethanol, and then 4.5 mL of 35 wt% nitric acid aqueous solution and 3.5 g of aluminum isopropoxide were added, and the mixture was stirred for 30 min, and then dried at 60 ° C for 24 h. The obtained product was calcined at 450 ° C in air atmosphere for 5 h to obtain mesoporous aluminum oxide; 1-2) Take 1g of mesoporous alumina and add it to 120mL of deionized water, and disperse it by ultrasonic for 15min. Then add 0.25g of zinc acetate and disperse it by ultrasonic for 30min to obtain a mixed dispersion. 1-3) Add 344 mg of citric acid, 285 mg of lutein, 103 mg of diethylenetriamine, and 89 mg of urea to the mixed dispersion, and disperse by ultrasonic for 15 min to obtain a carbon dot precursor solution; 1-4) The obtained carbon dot precursor solution was transferred to a polytetrafluoroethylene-lined reactor and reacted at 185°C for 10 hours. After the reaction was completed, it was cooled to room temperature, the product was centrifuged, and the obtained solid product was vacuum dried at 90°C for 12 hours to obtain mesoporous alumina loaded with carbon dots.

[0049] 2) Preparation of graphene oxide GO: 10g of graphite and 5g of sodium nitrate were added to 250mL of 98wt% concentrated sulfuric acid, stirred for 15min under ice bath conditions, then 35g of KMnO4 was added, stirred at 10-20℃ for 40min, heated to 35℃, and continued to stir for 10h, 400mL of deionized water was added to the product, the temperature was raised to 98℃ and maintained for 20min, and then 400mL of deionized water and 5mL of 25wt% H2O2 solution were added in sequence, and the mixture was allowed to stand for 60min. After the system was separated into layers, the supernatant was removed, and the product was washed with deionized water until neutral, and dried at 65℃ for 24h to obtain graphene oxide GO.

[0050] 3) Preparation of reduced graphene oxide r-GO: Take 1 g of graphene oxide and add it to 50 mL of DMF (dimethylformamide) solution, ultrasonically disperse it for 30 minutes, then add it to 15 mL of ethylenediamine, stir and reflux at 85°C for 24 hours, filter the product, wash it with DMF and ethanol in turn, vacuum dry it at 70°C for 12 hours, and grind it to obtain reduced graphite oxide.

[0051] 4) Preparation of doped modified graphene-aluminum-magnesium hydrotalcite composites: 4-1) Take 5.12g of Mg(NO3)2·6H2O, 7.5g of Al(NO3)2·9H2O, and 2.5g of sodium citrate and add them to 600mL of deionized water, and ultrasonicate for 15min to obtain precursor solution 1; 4-2) Take 2.5g of carbon dot-loaded mesoporous alumina and 3.8g of r-GO and add them into 500mL of deionized water, disperse them by ultrasonic for 30min, then add 0.776g of Ce(NO3)3, stir at 1000rpm for 15min, and obtain precursor solution 2; 4-3) Precursor solution 1 is added to precursor solution 2 under stirring, the pH value of the system is adjusted to 9.5-10.5 with an alkaline solution, ultrasonicated for 60 minutes, and the resulting mixture is transferred to a polytetrafluoroethylene-lined reactor, reacted at 140°C for 12 hours, filtered after the reaction, and the solid product is washed with deionized water until neutral, vacuum dried at 70°C for 12 hours, and ground to obtain a doped modified graphene-aluminum magnesium hydrotalcite composite; The alkaline solution is a mixture of NaOH and Na2CO3 in deionized water, with the concentration of NaOH being 1 mol / L and the concentration of Na2CO3 being 0.5 mol / L.

[0052] 5) The doped modified graphene-aluminum magnesium hydrotalcite composite is coated with an organic polymer to obtain a coated doped modified graphene-aluminum magnesium hydrotalcite composite: 5-1) 4 g of acrylic acid, 3.5 g of methyl methacrylate and 3.5 g of butyl acrylate were added to 80 mL of a mixed solution consisting of deionized water and ethanol in a volume ratio of 1:1, and stirred for 10 min to obtain a mixture 1; 5-2) 2 g of the doped modified graphene-aluminum magnesium hydrotalcite composite, 0.8 g of fatty alcohol polyoxyethylene ether ammonium sulfate, and 100 mL of ethanol were added into 150 mL of deionized water, and stirred at 800 rpm for 45 min to obtain a mixture 2; 5-3) Add 1 / 3 of the mass of mixture 1 to the mixture 2 under stirring, continue stirring for 15 minutes, add 0.08g of potassium persulfate, and then heat to 68°C and react for 1 hour; add the remaining mixture 1 dropwise to the product of step 1 under stirring, and complete the addition within 1.5 hours, then add 0.1g of potassium persulfate, raise the temperature to 75°C, and react for 3 hours to obtain a coated doped modified graphene-aluminum magnesium hydrotalcite composite.

[0053] Example 2 A high-performance polyvinyl chloride modified by composite doping of graphene-aluminum-magnesium hydrotalcite comprises the following raw material components in parts by weight: 100 parts of PVC resin; 4 parts of heat stabilizer; 2 parts of coupling agent; Plasticizer 7 parts; 19 parts of coated doped modified graphene-aluminum magnesium hydrotalcite composite.

[0054] The heat stabilizer is a mixture of calcium stearate and barium stearate in a mass ratio of 1:1, the coupling agent is silane coupling agent KH560, and the plasticizer is epoxy soybean oil.

[0055] The preparation method of the graphene-aluminum-magnesium hydrotalcite composite doped and modified high-performance polyvinyl chloride is as follows: According to the above weight ratio, PVC resin, heat stabilizer, coupling agent, plasticizer and coated doped modified graphene-aluminum-magnesium hydrotalcite composite were added to a mixer and stirred at 800 rpm for 30 minutes. The resulting mixture was added to an open mill and mixed at 165° C. for 20 minutes to obtain high-performance polyvinyl chloride doped and modified by graphene-aluminum-magnesium binary hydrotalcite composite.

[0056] The coated doped modified graphene-aluminum magnesium hydrotalcite composite is prepared by the following steps: 1) Preparation of mesoporous alumina loaded with carbon dots: 1-1) 1.5 g of polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer was added to 50 mL of ethanol, and then 4.5 mL of 35 wt% nitric acid aqueous solution and 3.5 g of aluminum isopropoxide were added, and the mixture was stirred for 30 min, and then dried at 60 ° C for 24 h. The obtained product was calcined at 450 ° C in air atmosphere for 5 h to obtain mesoporous aluminum oxide; 1-2) Take 1g of mesoporous alumina and add it to 120mL of deionized water, and disperse it by ultrasonic for 15min. Then add 0.25g of zinc acetate and disperse it by ultrasonic for 30min to obtain a mixed dispersion. 1-3) Add 344 mg of citric acid, 285 mg of lutein, 103 mg of diethylenetriamine, and 89 mg of urea to the mixed dispersion, and disperse by ultrasonic for 15 min to obtain a carbon dot precursor solution; 1-4) The obtained carbon dot precursor solution was transferred to a polytetrafluoroethylene-lined reactor and reacted at 185°C for 10 hours. After the reaction was completed, it was cooled to room temperature, the product was centrifuged, and the obtained solid product was vacuum dried at 90°C for 12 hours to obtain mesoporous alumina loaded with carbon dots.

[0057] 2) Preparation of graphene oxide GO: 10g of graphite and 5g of sodium nitrate were added to 250mL of 98wt% concentrated sulfuric acid, stirred for 15min under ice bath conditions, then 35g of KMnO4 was added, stirred at 10-20℃ for 40min, heated to 35℃, and continued to stir for 10h, 400mL of deionized water was added to the product, the temperature was raised to 98℃ and maintained for 20min, and then 400mL of deionized water and 5mL of 25wt% H2O2 solution were added in sequence, and the mixture was allowed to stand for 60min. After the system was separated into layers, the supernatant was removed, and the product was washed with deionized water until neutral, and dried at 65℃ for 24h to obtain graphene oxide GO.

[0058] 3) Preparation of reduced graphene oxide r-GO: Take 1 g of graphene oxide and add it to 50 mL of DMF (dimethylformamide) solution, ultrasonically disperse it for 30 minutes, then add it to 15 mL of ethylenediamine, stir and reflux at 85°C for 24 hours, filter the product, wash it with DMF and ethanol in turn, vacuum dry it at 70°C for 12 hours, and grind it to obtain reduced graphite oxide.

[0059] 4) Preparation of doped modified graphene-aluminum-magnesium hydrotalcite composites: 4-1) Take 5.12g of Mg(NO3)2·6H2O, 7.5g of Al(NO3)2·9H2O, and 2.5g of sodium citrate and add them to 600mL of deionized water, and ultrasonicate for 15min to obtain precursor solution 1; 4-2) Take 2.3g of carbon dot-loaded mesoporous alumina and 3.8g of r-GO and add them into 500mL of deionized water, disperse them by ultrasonic for 30min, then add 0.776g of Ce(NO3)3, stir at 1000rpm for 15min, and obtain precursor solution 2; 4-3) Precursor solution 1 is added to precursor solution 2 under stirring, the pH value of the system is adjusted to 9.5-10.5 with an alkaline solution, ultrasonicated for 60 minutes, and the resulting mixture is transferred to a polytetrafluoroethylene-lined reactor, reacted at 140°C for 12 hours, filtered after the reaction, and the solid product is washed with deionized water until neutral, vacuum dried at 70°C for 12 hours, and ground to obtain a doped modified graphene-aluminum magnesium hydrotalcite composite; The alkaline solution is a mixture of NaOH and Na2CO3 in deionized water, with the concentration of NaOH being 1 mol / L and the concentration of Na2CO3 being 0.5 mol / L.

[0060] 5) The doped modified graphene-aluminum magnesium hydrotalcite composite is coated with an organic polymer to obtain a coated doped modified graphene-aluminum magnesium hydrotalcite composite: 5-1) 4 g of acrylic acid, 3.5 g of methyl methacrylate and 3.5 g of butyl acrylate were added to 80 mL of a mixed solution consisting of deionized water and ethanol in a volume ratio of 1:1, and stirred for 10 min to obtain a mixture 1; 5-2) 1.8 g of doped modified graphene-aluminum magnesium hydrotalcite composite, 0.8 g of fatty alcohol polyoxyethylene ether ammonium sulfate, and 100 mL of ethanol were added into 150 mL of deionized water, and stirred at 800 rpm for 45 min to obtain a mixture 2; 5-3) Add 1 / 3 of the mass of mixture 1 to the mixture 2 under stirring, continue stirring for 15 minutes, add 0.08g of potassium persulfate, and then heat to 68°C and react for 1 hour; add the remaining mixture 1 dropwise to the product of step 1 under stirring, and complete the addition within 1.5 hours, then add 0.1g of potassium persulfate, raise the temperature to 75°C, and react for 3 hours to obtain a coated doped modified graphene-aluminum magnesium hydrotalcite composite.

[0061] Example 3 A high-performance polyvinyl chloride modified by composite doping of graphene-aluminum-magnesium hydrotalcite comprises the following raw material components in parts by weight: 100 parts of PVC resin; 4 parts of heat stabilizer; 2 parts of coupling agent; Plasticizer 7 parts; 24 parts of coated doped modified graphene-aluminum-magnesium hydrotalcite composite.

[0062] The heat stabilizer is a mixture of calcium stearate and barium stearate in a mass ratio of 1:1, the coupling agent is silane coupling agent KH560, and the plasticizer is epoxy soybean oil.

[0063] The preparation method of the graphene-aluminum-magnesium hydrotalcite composite doped and modified high-performance polyvinyl chloride is as follows: According to the above weight ratio, PVC resin, heat stabilizer, coupling agent, plasticizer and coated doped modified graphene-aluminum-magnesium hydrotalcite composite were added to a mixer and stirred at 800 rpm for 30 minutes. The resulting mixture was added to an open mill and mixed at 165° C. for 20 minutes to obtain high-performance polyvinyl chloride doped and modified by graphene-aluminum-magnesium binary hydrotalcite composite.

[0064] The coated doped modified graphene-aluminum magnesium hydrotalcite composite is prepared by the following steps: 1) Preparation of mesoporous alumina loaded with carbon dots: 1-1) 1.5 g of polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer was added to 50 mL of ethanol, and then 4.5 mL of 35 wt% nitric acid aqueous solution and 3.5 g of aluminum isopropoxide were added, and the mixture was stirred for 30 min, and then dried at 60 ° C for 24 h. The obtained product was calcined at 450 ° C in air atmosphere for 5 h to obtain mesoporous aluminum oxide; 1-2) 1.2 g of mesoporous alumina was added to 120 mL of deionized water and ultrasonically dispersed for 15 min, then 0.25 g of zinc acetate was added and ultrasonically dispersed for 30 min to obtain a mixed dispersion; 1-3) Add 344 mg of citric acid, 285 mg of lutein, 103 mg of diethylenetriamine, and 89 mg of urea to the mixed dispersion, and disperse by ultrasonic for 15 min to obtain a carbon dot precursor solution; 1-4) The obtained carbon dot precursor solution was transferred to a polytetrafluoroethylene-lined reactor and reacted at 185°C for 10 hours. After the reaction was completed, it was cooled to room temperature, the product was centrifuged, and the obtained solid product was vacuum dried at 90°C for 12 hours to obtain mesoporous alumina loaded with carbon dots.

[0065] 2) Preparation of graphene oxide GO: 10g of graphite and 5g of sodium nitrate were added to 250mL of 98wt% concentrated sulfuric acid, stirred for 15min under ice bath conditions, then 35g of KMnO4 was added, stirred at 10-20℃ for 40min, heated to 35℃, and continued to stir for 10h, 400mL of deionized water was added to the product, the temperature was raised to 98℃ and maintained for 20min, and then 400mL of deionized water and 5mL of 25wt% H2O2 solution were added in sequence, and the mixture was allowed to stand for 60min. After the system was separated into layers, the supernatant was removed, and the product was washed with deionized water until neutral, and dried at 65℃ for 24h to obtain graphene oxide GO.

[0066] 3) Preparation of reduced graphene oxide r-GO: Take 1 g of graphene oxide and add it to 50 mL of DMF (dimethylformamide) solution, ultrasonically disperse it for 30 minutes, then add it to 15 mL of ethylenediamine, stir and reflux at 85°C for 24 hours, filter the product, wash it with DMF and ethanol in turn, vacuum dry it at 70°C for 12 hours, and grind it to obtain reduced graphite oxide.

[0067] 4) Preparation of doped modified graphene-aluminum-magnesium hydrotalcite composites: 4-1) Take 5.12g of Mg(NO3)2·6H2O, 7.5g of Al(NO3)2·9H2O, and 2.5g of sodium citrate and add them to 600mL of deionized water, and ultrasonicate for 15min to obtain precursor solution 1; 4-2) Take 2.5g of carbon dot-loaded mesoporous alumina and 3.8g of r-GO and add them into 500mL of deionized water, disperse them by ultrasonic for 30min, then add 0.776g of Ce(NO3)3, stir at 1000rpm for 15min, and obtain precursor solution 2; 4-3) Precursor solution 1 is added to precursor solution 2 under stirring, the pH value of the system is adjusted to 9.5-10.5 with an alkaline solution, ultrasonicated for 60 minutes, and the resulting mixture is transferred to a polytetrafluoroethylene-lined reactor, reacted at 140°C for 12 hours, filtered after the reaction, and the solid product is washed with deionized water until neutral, vacuum dried at 70°C for 12 hours, and ground to obtain a doped modified graphene-aluminum magnesium hydrotalcite composite; The alkaline solution is a mixture of NaOH and Na2CO3 in deionized water, with the concentration of NaOH being 1 mol / L and the concentration of Na2CO3 being 0.5 mol / L.

[0068] 5) The doped modified graphene-aluminum magnesium hydrotalcite composite is coated with an organic polymer to obtain a coated doped modified graphene-aluminum magnesium hydrotalcite composite: 5-1) 5 g of acrylic acid, 3 g of methyl methacrylate, and 3.5 g of butyl acrylate were added to 80 mL of a mixed solution consisting of deionized water and ethanol in a volume ratio of 1:1, and stirred for 10 min to obtain a mixture 1; 5-2) 1.8 g of doped modified graphene-aluminum magnesium hydrotalcite composite, 0.8 g of fatty alcohol polyoxyethylene ether ammonium sulfate, and 100 mL of ethanol were added into 150 mL of deionized water, and stirred at 800 rpm for 45 min to obtain a mixture 2; 5-3) Add 1 / 3 of the mass of mixture 1 to the mixture 2 under stirring, continue stirring for 15 minutes, add 0.08g of potassium persulfate, and then heat to 68°C and react for 1 hour; add the remaining mixture 1 dropwise to the product of step 1 under stirring, and complete the addition within 1.5 hours, then add 0.1g of potassium persulfate, raise the temperature to 75°C, and react for 3 hours to obtain a coated doped modified graphene-aluminum magnesium hydrotalcite composite.

[0069] Example 4 A high-performance polyvinyl chloride modified by composite doping of graphene-aluminum-magnesium hydrotalcite comprises the following raw material components in parts by weight: 100 parts of PVC resin; 4 parts of heat stabilizer; 2 parts of coupling agent; Plasticizer 7 parts; 21 parts of coated doped modified graphene-aluminum-magnesium hydrotalcite composite.

[0070] The heat stabilizer is a mixture of calcium stearate and barium stearate in a mass ratio of 1:1, the coupling agent is silane coupling agent KH560, and the plasticizer is epoxy soybean oil.

[0071] The preparation method of the graphene-aluminum-magnesium hydrotalcite composite doped and modified high-performance polyvinyl chloride is as follows: According to the above weight ratio, PVC resin, heat stabilizer, coupling agent, plasticizer and coated doped modified graphene-aluminum-magnesium hydrotalcite composite were added to a mixer and stirred at 800 rpm for 30 minutes. The resulting mixture was added to an open mill and mixed at 165° C. for 20 minutes to obtain high-performance polyvinyl chloride doped and modified by graphene-aluminum-magnesium binary hydrotalcite composite.

[0072] The coated doped modified graphene-aluminum magnesium hydrotalcite composite is prepared by the following steps: 1) Preparation of mesoporous alumina loaded with carbon dots: 1-1) 1.5 g of polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer was added to 50 mL of ethanol, and then 4.5 mL of 35 wt% nitric acid aqueous solution and 3.5 g of aluminum isopropoxide were added, and the mixture was stirred for 30 min, and then dried at 60 ° C for 24 h. The obtained product was calcined at 450 ° C in air atmosphere for 5 h to obtain mesoporous aluminum oxide; 1-2) Take 1g of mesoporous alumina and add it to 120mL of deionized water, and disperse it by ultrasonic for 15min. Then add 0.3g of zinc acetate and disperse it by ultrasonic for 30min to obtain a mixed dispersion. 1-3) Add 344 mg of citric acid, 285 mg of lutein, 103 mg of diethylenetriamine, and 89 mg of urea to the mixed dispersion, and disperse by ultrasonic for 15 min to obtain a carbon dot precursor solution; 1-4) The obtained carbon dot precursor solution was transferred to a polytetrafluoroethylene-lined reactor and reacted at 185°C for 10 hours. After the reaction was completed, it was cooled to room temperature, the product was centrifuged, and the obtained solid product was vacuum dried at 90°C for 12 hours to obtain mesoporous alumina loaded with carbon dots.

[0073] 2) Preparation of graphene oxide GO: 10g of graphite and 5g of sodium nitrate were added to 250mL of 98wt% concentrated sulfuric acid, stirred for 15min under ice bath conditions, then 35g of KMnO4 was added, stirred at 10-20℃ for 40min, heated to 35℃, and continued to stir for 10h, 400mL of deionized water was added to the product, the temperature was raised to 98℃ and maintained for 20min, and then 400mL of deionized water and 5mL of 25wt% H2O2 solution were added in sequence, and the mixture was allowed to stand for 60min. After the system was separated into layers, the supernatant was removed, and the product was washed with deionized water until neutral, and dried at 65℃ for 24h to obtain graphene oxide GO.

[0074] 3) Preparation of reduced graphene oxide r-GO: Take 1 g of graphene oxide and add it to 50 mL of DMF (dimethylformamide) solution, ultrasonically disperse it for 30 minutes, then add it to 15 mL of ethylenediamine, stir and reflux at 85°C for 24 hours, filter the product, wash it with DMF and ethanol in turn, vacuum dry it at 70°C for 12 hours, and grind it to obtain reduced graphite oxide.

[0075] 4) Preparation of doped modified graphene-aluminum-magnesium hydrotalcite composites: 4-1) Take 5.12g of Mg(NO3)2·6H2O, 7.5g of Al(NO3)2·9H2O, and 2.5g of sodium citrate and add them to 600mL of deionized water, and ultrasonicate for 15min to obtain precursor solution 1; 4-2) Take 2.8g of carbon dot-loaded mesoporous alumina and 3.5g of r-GO and add them into 500mL of deionized water, disperse them by ultrasonic for 30min, then add 0.776g of Ce(NO3)3, stir at 1000rpm for 15min, and obtain precursor solution 2; 4-3) Precursor solution 1 is added to precursor solution 2 under stirring, the pH value of the system is adjusted to 9.5-10.5 with an alkaline solution, ultrasonicated for 60 minutes, and the resulting mixture is transferred to a polytetrafluoroethylene-lined reactor, reacted at 140°C for 12 hours, filtered after the reaction, and the solid product is washed with deionized water until neutral, vacuum dried at 70°C for 12 hours, and ground to obtain a doped modified graphene-aluminum magnesium hydrotalcite composite; The alkaline solution is a mixture of NaOH and Na2CO3 in deionized water, with the concentration of NaOH being 1 mol / L and the concentration of Na2CO3 being 0.5 mol / L.

[0076] 5) The doped modified graphene-aluminum magnesium hydrotalcite composite is coated with an organic polymer to obtain a coated doped modified graphene-aluminum magnesium hydrotalcite composite: 5-1) 6 g of acrylic acid, 3 g of methyl methacrylate and 3 g of butyl acrylate were added to 80 mL of a mixed solution consisting of deionized water and ethanol in a volume ratio of 1:1, and stirred for 10 min to obtain a mixture 1; 5-2) 2 g of the doped modified graphene-aluminum magnesium hydrotalcite composite, 0.8 g of fatty alcohol polyoxyethylene ether ammonium sulfate, and 100 mL of ethanol were added into 150 mL of deionized water, and stirred at 800 rpm for 45 min to obtain a mixture 2; 5-3) Add 1 / 3 of the mass of mixture 1 to the mixture 2 under stirring, continue stirring for 15 minutes, add 0.08g of potassium persulfate, and then heat to 68°C and react for 1 hour; add the remaining mixture 1 dropwise to the product of step 1 under stirring, and complete the addition within 1.5 hours, then add 0.1g of potassium persulfate, raise the temperature to 75°C, and react for 3 hours to obtain a coated doped modified graphene-aluminum magnesium hydrotalcite composite.

[0077] Comparative Example 1 This example is basically the same as Example 1, except that: In this example, the coated doped modified graphene-aluminum magnesium hydrotalcite composite is prepared by the following steps: 1) preparing graphene oxide GO, the specific steps are the same as those in Example 1; 2) preparing reduced graphene oxide r-GO, the specific steps are the same as those in Example 1; 3) Preparation of doped modified graphene-aluminum-magnesium hydrotalcite composites: 3-1) Take 5.12g of Mg(NO3)2·6H2O, 7.5g of Al(NO3)2·9H2O, and 2.5g of sodium citrate and add them to 600mL of deionized water, and ultrasonicate for 15min to obtain precursor solution 1; 3-2) 3.8 g of r-GO was added into 500 mL of deionized water, and ultrasonically dispersed for 30 min. Then 0.776 g of Ce(NO3)3 was added, and stirred at 1000 rpm for 15 min to obtain precursor solution 2. 3-3) Precursor solution 1 is added to precursor solution 2 under stirring, the pH value of the system is adjusted to 9.5-10.5 with an alkaline solution, ultrasonicated for 60 minutes, and the resulting mixture is transferred to a polytetrafluoroethylene-lined reactor, reacted at 140° C. for 12 hours, filtered after the reaction, and the solid product is washed with deionized water until neutral, vacuum dried at 70° C. for 12 hours, and ground to obtain a doped modified graphene-aluminum magnesium hydrotalcite composite; The alkaline solution is a mixture of NaOH and Na2CO3 in deionized water, with the concentration of NaOH being 1 mol / L and the concentration of Na2CO3 being 0.5 mol / L.

[0078] 4) The doped modified graphene-aluminum-magnesium hydrotalcite composite is coated with an organic polymer to obtain a coated doped modified graphene-aluminum-magnesium hydrotalcite composite. The specific steps are the same as those in Example 1.

[0079] Comparative Example 2 This example is basically the same as Example 1, except that: In this example, in the preparation step of the coated doped modified graphene-aluminum magnesium hydrotalcite composite, mesoporous alumina is used instead of the mesoporous alumina loaded with carbon dots in Example 1. The preparation method of the mesoporous alumina is as follows: 1.5 g of polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer is added to 50 mL of ethanol, and then 4.5 mL of a 35 wt% nitric acid aqueous solution and 3.5 g of aluminum isopropoxide are added, the reaction is stirred for 30 minutes, and then dried at 60°C for 24 hours. The product is calcined at 450°C in an air atmosphere for 5 hours to obtain mesoporous alumina.

[0080] Comparative Example 3 This example is basically the same as Example 1, except that: In this example, the preparation method of mesoporous alumina loaded with carbon dots is: 1-1) 1.5 g of polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer was added to 50 mL of ethanol, and then 4.5 mL of 35 wt% nitric acid aqueous solution and 3.5 g of aluminum isopropoxide were added, and the mixture was stirred for 30 min, and then dried at 60 ° C for 24 h. The obtained product was calcined at 450 ° C in air atmosphere for 5 h to obtain mesoporous aluminum oxide; 1-2) Take 1g of mesoporous alumina and add it into 120mL of deionized water, and disperse it by ultrasonic for 30min to obtain a mixed dispersion; 1-3) Add 344 mg of citric acid, 285 mg of lutein, 103 mg of diethylenetriamine, and 89 mg of urea to the mixed dispersion, and disperse by ultrasonic for 15 min to obtain a carbon dot precursor solution; 1-4) The obtained carbon dot precursor solution was transferred to a polytetrafluoroethylene-lined reactor and reacted at 185°C for 10 hours. After the reaction was completed, it was cooled to room temperature, the product was centrifuged, and the obtained solid product was vacuum dried at 90°C for 12 hours to obtain mesoporous alumina loaded with carbon dots.

[0081] Comparative Example 4 This example is basically the same as Example 1, except that: The high-performance polyvinyl chloride modified by graphene-aluminum-magnesium hydrotalcite composite doping in this example includes the following raw material components in parts by weight: 100 parts of PVC resin; 4 parts of heat stabilizer; 2 parts of coupling agent; Plasticizer 7 parts; 21 parts of doped modified graphene-aluminum-magnesium hydrotalcite composite.

[0082] The preparation method of the doped modified graphene-aluminum-magnesium hydrotalcite composite is the same as that in Example 1.

[0083] Performance Testing 1. Free radical scavenging ability test The carbon dot-loaded mesoporous alumina (Al2O3@Zn-CDs) prepared in Example 1 and the carbon dot-loaded mesoporous alumina (Al2O3@CDs) prepared in Comparative Example 3 were tested for free radical scavenging ability according to the following methods.

[0084] The sample was prepared into a dispersion with a concentration of 1 mg / mL using ethanol, and the nitrogen free radical (DPPH) scavenging ability test kit (Sangon Biotech (Shanghai) Co., Ltd.) was used to detect the antioxidant performance of the magnetic bead working solution over a certain period of time.

[0085] Principle of determination: DPPH free radical has a single electron, its alcohol solution is purple, and has strong absorption at 515nm. When an antioxidant is present, DPPH free radical is scavenged, the color of its solution becomes lighter, and the absorbance at 515nm decreases. Within a certain range, the change in its absorbance is proportional to the degree of free radical scavenging. In this kit, the degree of absorbance decrease reflects the ability of the sample to scavenge DPPH free radicals. The greater the decrease, the stronger the free radical scavenging ability.

[0086] Reference Figure 1 , is the test result. It can be seen that the Al2O3@Zn-CDs prepared in Example 1 can provide a long-lasting free radical scavenging effect, and by comparing with Al2O3@CDs, it can be found that zinc doping improves the free radical scavenging ability of carbon dots.

[0087] 2. The high-performance polyvinyl chloride prepared in the examples and comparative examples was hot pressed into samples of a certain thickness at 170°C ± 5°C on an electric tablet press (BP-8170-A, Dongguan Baopin Precision Instrument Co., Ltd.), and cut into specified sizes for the following tests: 1. Tensile strength: Tested in accordance with standard GB / T1040.1-2018; 2. Bending strength: Tested in accordance with standard GB / T 9341-2008; 3. Limiting oxygen index (LOI): Tested in accordance with standard GB / T 2406-80; 4. Heat deformation temperature test: Test in accordance with standard GB / T 1634.3-2004; 5. Heat aging performance: refer to the standard "GBT7141-2008- Plastic Thermal Aging Test Method" for heat aging, 100℃, 240h, then test the tensile strength and flexural strength according to the above method, and calculate the tensile strength retention rate and flexural strength retention rate.

[0088] The test results are shown in Table 1 and Figure 2-7 As shown: Table 1 It can be seen from the test results that the high-performance polyvinyl chloride prepared in Examples 1-4 has excellent anti-aging performance, thermal stability, flame retardant performance and mechanical properties. In the coated doped modified graphene-aluminum magnesium hydrotalcite composite system in Comparative Example 1, no mesoporous alumina loaded with carbon dots was added, resulting in a significant decrease in anti-aging performance and thermal stability; in Comparative Example 2, no carbon dots were loaded on the mesoporous alumina, resulting in poor anti-aging performance and thermal stability; the decrease in anti-aging performance and thermal stability in Comparative Example 3 was attributed to the lack of zinc doping in the carbon dots; the decrease in comprehensive performance in Comparative Example 4 was attributed to the lack of polyacrylate film, which affected the dispersibility of the doped modified graphene-aluminum magnesium hydrotalcite composite in the polyvinyl chloride organic system and restricted the enhancement effect of each component on PVC.

[0089] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation modes. They can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to specific details.

Claims

1. A high-performance polyvinyl chloride modified by graphene-aluminum-magnesium hydrotalcite composite doping, characterized in that: The invention comprises the following raw material components by weight: 100 parts of PVC resin; 3-5 parts of heat stabilizer; 1-2 parts of coupling agent; 5-14 parts of plasticizer; 8-26 parts of the coated doped modified graphene-aluminum-magnesium hydrotalcite composite.

2. The high-performance polyvinyl chloride modified by composite doping of graphene-aluminum-magnesium hydrotalcite according to claim 1, characterized in that: The heat stabilizer is at least one of calcium stearate, barium stearate and zinc stearate; The coupling agent is at least one of silane coupling agent KH560 and silane coupling agent KH570.

3. The high-performance polyvinyl chloride modified by composite doping of graphene-aluminum-magnesium hydrotalcite according to claim 1, characterized in that: The plasticizer is at least one of di(2-ethylhexyl) phthalate and epoxy soybean oil.

4. The high-performance polyvinyl chloride modified by composite doping of graphene-aluminum-magnesium hydrotalcite according to claim 1, characterized in that: The coated doped modified graphene-aluminum-magnesium hydrotalcite composite is prepared by the following steps: 1) Preparation of mesoporous alumina loaded with carbon dots; 2) Preparation of graphene oxide GO; 3) Preparation of reduced graphene oxide r-GO; 4) Preparation of doped modified graphene-aluminum-magnesium hydrotalcite composites; 5) The doped modified graphene-aluminum magnesium hydrotalcite composite is coated with an organic polymer to prepare a coated doped modified graphene-aluminum magnesium hydrotalcite composite.

5. The high-performance polyvinyl chloride modified by composite doping of graphene-aluminum-magnesium hydrotalcite according to claim 4, characterized in that: Step 1) is as follows: 1-1) 0.5-3 g of polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer is added to 25-100 mL of ethanol, and then 2-9 mL of 35 wt% nitric acid aqueous solution and 1.75-7 g of aluminum isopropoxide are added, and the mixture is stirred for reaction for 15-30 min, and then dried at 50-80° C. for 12-36 h. The obtained product is calcined at 400-500° C. in an air atmosphere for 3-10 h to obtain mesoporous aluminum oxide; 1-2) Take 0.5-2g of mesoporous alumina and add it to 50-200mL of deionized water, and disperse it by ultrasonic for 5-30min. Then, add 0.1-0.5g of zinc acetate and disperse it by ultrasonic for 15-60min to obtain a mixed dispersion; 1-3) adding 172-688 mg of citric acid, 142-370 mg of lutein, 50-206 mg of diethylenetriamine, and 45-180 mg of urea to the mixed dispersion, and performing ultrasonic dispersion for 5-30 min to obtain a carbon dot precursor solution; 1-4) The obtained carbon dot precursor solution is transferred to a polytetrafluoroethylene-lined reactor, and the reaction is carried out at 175-210° C. for 5-24 hours. After the reaction is completed, the reaction is cooled to room temperature, the product is centrifuged, and the obtained solid product is vacuum dried at 70-100° C. for 6-24 hours to obtain mesoporous alumina loaded with carbon dots.

6. The high-performance polyvinyl chloride modified by composite doping of graphene-aluminum-magnesium hydrotalcite according to claim 5, characterized in that: Step 2) specifically includes: 5-20g of graphite and 2.5-10g of sodium nitrate are added to 100-500mL of 98wt% concentrated sulfuric acid, and the mixture is stirred for reaction under ice bath conditions for 5-30min. Then, 17-70g of KMnO4 is added, and the mixture is stirred for 20-60min at 10-20°C, and the mixture is heated to 30-35°C, and the mixture is stirred for reaction for 5-20h. 200-800mL of deionized water is added to the product, and the mixture is heated to 90-98°C and maintained for 10-40min. Then, 200-800mL of deionized water and 2-10mL of 25wt% H2O2 solution are added in sequence, and the mixture is allowed to stand for 30-120min. After the system is separated into layers, the supernatant is removed, and the obtained product is washed with deionized water until neutralized, and then dried at 60-80°C for 12-36h to obtain graphene oxide GO.

7. The high-performance polyvinyl chloride modified by composite doping of graphene-aluminum-magnesium hydrotalcite according to claim 6, characterized in that: Step 3) specifically includes: Take 0.5-2g of graphene oxide and add it to 25-100mL DMF solution, ultrasonically disperse it for 15-60min, then add it to 5-30mL ethylenediamine, stir and reflux at 70-90°C for 12-48h, filter the product, wash it with DMF and ethanol in turn, vacuum dry it at 60-90°C for 6-24h, grind it to obtain reduced graphite oxide.

8. The high-performance polyvinyl chloride modified by composite doping of graphene-aluminum-magnesium hydrotalcite according to claim 7, characterized in that: Step 4) is as follows: 4-1) Take 2.6-11g of Mg(NO3)2·6H2O, 3.5-15g of Al(NO3)2·9H2O, and 1.25-5g of sodium citrate and add them to 300-1200mL of deionized water, and ultrasonicate for 10-30min to obtain precursor solution 1; 4-2) 1.25-5g of carbon dot-loaded mesoporous alumina and 1.9-7.6g of r-GO were added into 250-1000mL of deionized water, and ultrasonically dispersed for 10-60min. Then, 0.35-1.5g of Ce(NO3)3 was added, and stirred at 500-2000rpm for 10-60min to obtain precursor solution 2; 4-3) Precursor solution 1 is added to precursor solution 2 under stirring, the pH value of the system is adjusted to 9.5-10.5 with an alkaline solution, ultrasonicated for 30-120 minutes, and the resulting mixture is transferred to a polytetrafluoroethylene-lined reactor, reacted at 130-150° C. for 6-24 hours, filtered after the reaction, and the solid product is washed with deionized water until neutral, vacuum dried at 60-90° C. for 6-24 hours, and ground to obtain a doped modified graphene-aluminum magnesium hydrotalcite composite; The alkaline solution is a mixture of NaOH and Na2CO3 in deionized water, wherein the concentration of NaOH is 0.5-2 mol / L and the concentration of Na2CO3 is 0.25-1 mol / L.

9. The high-performance polyvinyl chloride modified by composite doping of graphene-aluminum-magnesium hydrotalcite according to claim 8, characterized in that: Step 5) specifically includes: 5-1) 2-8 g of acrylic acid, 1.7-7 g of methyl methacrylate, and 1.7-7 g of butyl acrylate were added to 40-160 mL of a mixed solution consisting of deionized water and ethanol in a volume ratio of 1:1, and stirred for 5-20 min to obtain a mixture 1; 5-2) 1-4 g of the doped modified graphene-aluminum magnesium hydrotalcite composite, 0.4-1.6 g of fatty alcohol polyoxyethylene ether ammonium sulfate, and 50-200 mL of ethanol were added into 75-300 mL of deionized water, and stirred at 400-1500 rpm for 30-90 min to obtain a mixture 2; 5-3) Add 1 / 3 of the mass of mixture 1 to the mixed solution 2 under stirring, continue stirring for 5-30 minutes, add 0.04-0.16g of potassium persulfate, and then heat to 65-72°C and react for 0.5-2h; add the remaining mixture 1 dropwise to the product of step 1 under stirring, and complete the addition within 1-3h, then add 0.05-0.2g of potassium persulfate, raise the temperature to 73-78°C, and react for 1.5-6h to obtain a coated doped modified graphene-aluminum magnesium hydrotalcite composite.

10. A method for preparing high-performance polyvinyl chloride modified by composite doping of graphene-aluminum-magnesium hydrotalcite according to any one of claims 1 to 9, characterized in that: The following steps are involved: The PVC resin, heat stabilizer, coupling agent, plasticizer and coated doped modified graphene-aluminum magnesium hydrotalcite composite are stirred at a rotation speed of 400-1200 rpm for 15-60 minutes, and the obtained mixture is kneaded at 150-170° C. for 5-30 minutes to obtain high-performance polyvinyl chloride doped and modified by graphene-aluminum magnesium binary hydrotalcite composite.

Citation Information

Patent Citations

  • An aging-resistant polyvinyl chloride composite material and its preparation method

    CN111518345B

  • Preparation method of anti-aging polyvinyl chloride composite material

    CN118599242A